Long-acting reversible contraception with etonogestrel implants in female macaques (Macaca mulatta and Macaca fascicularis) - Maaskant, Annemiek; Scarsi, Kimberly K.; Meijer, Lisette; Roubos, Sandra; Louwerse, Annet L.; Remarque, Edmond J.; Langermans, Jan A. M.; Stammes, Marieke A.; Bakker, Jaco (Frontiers in Veterinary Science, 2024)
Contraception is often required for management and population control purposes in group housed and free roaming non-human primates. Long-acting reversible contraceptives, including subdermal progestin-releasing implants, are preferred as they eliminate challenges associated with frequent administration. Etonogestrel (ENG)-releasing subdermal implants are reversible, long acting for at least three years, and commercially available for human use as Implanon  or Nexplanon  . A retrospective analysis was performed detailing the contraceptive effectiveness, and reversibility of subdermal placement of 1 /4 or 1 /3 of an ENG implant (68mg/implant) in 129 female rhesus macaques (Macaca mulatta) and 67 cynomolgus macaques (Macaca fascicularis) at the Biomedical Primate Research Centre (Rijswijk, Netherlands). Furthermore, single cross sectional ENG serum concentrations were measured for 16 rhesus-and 10 cynomolgus macaques, and hemoglobin and blood chemistry pre ENG and at timepoints >0.5, >1.5 and >2.5 year post ENG insertion were evaluated for 24 rhesus macaques.Finally, data were obtained by trans-abdominal ultrasound regarding the influence of ENG on uterine volume and endometrial thickness in 14 rhesus-and 11 cynomolgus macaques. As a contraceptive ENG was in 99.80% (CI 93.50-99.99) and 99.95% (CI 99.95-100) effective in rhesus-and cynomolgus macaques, respectively. Prolonged ENG durations of implant use in 14 rhesus macaques (range 3.1-5.0 years) and eight cynomolgus macaques (range 3.2-4.0 years) resulted in no unintended pregnancies. A total of 17 female macaques were allowed to breed after ENG removal and 14 (82%) females had an uneventful delivery. Serum ENG concentrations with a median ENG duration of 1.2 years (range 0.1-6.0 years) and 1.9 years (range 0.6-4.7 years) resulted in median concentrations of 112 pg/mL (range 0-305 pg/mL) and 310 pg/mL (range 183-382 pg/mL) for rhesus-and cynomolgus macaques, respectively.ENG had no clinical effect on hemoglobin and blood chemistry parameters nor on the thickness of the endometrial lining or uterus volume. This study indicates that both 1 /4 and 1 /3 of an ENG implant is an effective, long-acting, reversible and a safe contraceptive to use in macaques.